1999
DOI: 10.1063/1.1852751
|View full text |Cite
|
Sign up to set email alerts
|

Micro-spectroscopic investigation of selenium-bearing minerals from the Western US Phosphate Resource Area

Abstract: Mining activities in the US Western Phosphate Resource Area ͑WPRA͒ have released Se into the environment. Selenium has several different oxidation states and species, each having varying degrees of solubility, reactivity, and bioavailability. In this study we are investigating the speciation of Se in mine-waste rocks. Selenium speciation was determined using bulk and micro-x-ray absorption spectroscopy ͑XAS͒, as well as micro-x-ray fluorescence mapping. Rocks used for bulk-XAS were ground into fine powders. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 8 publications
2
41
1
Order By: Relevance
“…Sample spectra exhibited noisier and more complex oscillations compared to the standards (Figure 3 and in Figure S7 in the SI) due to the lower concentration of Se (max 670 ppm in euhedral grains; Table 2). The fingerprints in k-space between both POI and the synthetic ferroselite 29 showed that both spectra were comparable in phase but with smaller oscillatory amplitudes at low wavenumbers. The sample spectra were clearly out of phase with the seleno-L-cysteine, Se sulfide, and elemental Se standards (Figures S7 and S10 in the SI).…”
Section: Bulk Composition and Se Distribution In The Variousmentioning
confidence: 99%
See 4 more Smart Citations
“…Sample spectra exhibited noisier and more complex oscillations compared to the standards (Figure 3 and in Figure S7 in the SI) due to the lower concentration of Se (max 670 ppm in euhedral grains; Table 2). The fingerprints in k-space between both POI and the synthetic ferroselite 29 showed that both spectra were comparable in phase but with smaller oscillatory amplitudes at low wavenumbers. The sample spectra were clearly out of phase with the seleno-L-cysteine, Se sulfide, and elemental Se standards (Figures S7 and S10 in the SI).…”
Section: Bulk Composition and Se Distribution In The Variousmentioning
confidence: 99%
“…Se K-edge μ-XANES spectra from POIa and POIb and selected standards. We also included the Se(-I) ferroselite standard from Ryser et al 29 but note that the spectral position in this spectrum is offset, yet the general shape and amplitude of the spectrum can be compared with our data. Se Chemical Environment and Bonding Characteristics.…”
Section: Bulk Composition and Se Distribution In The Variousmentioning
confidence: 99%
See 3 more Smart Citations